Risk Factors of Residual Dizziness After Successful Treatment for Benign Paroxysmal Positional Vertigo in Middle-Aged and Older Adults - Fu, Wei; He, Feng; Bai, Ya; An, Xinyue; Shi, Ying; Han, Junliang; Wang, Xiaoming (Frontiers in Neurology, 2022)
Objective The purpose of this study was to analyze risk factors of residual dizziness (RD) after successful treatment for benign paroxysmal positional vertigo (BPPV) in middle-aged and older adults. Methods 181 patients with BPPV, after successful canalith repositioning maneuver (CRM) treatment, were recruited. All patients were divided into the middle-aged group (aged 45–59 years, n = 101) and the older group (over 60 years, n = 80). The clinical characteristics were recorded, including age, gender, numbers of maneuvers, involved canal, affected side, RD, comorbidities, dizziness handicap inventory score, and generalized anxiety disorder's 7-item scale score. Results The incidence of RD in the older group was significantly higher than that of the middle-aged group (p = 0.033). Multivariate logistic regression analysis shows that age (odds ratio = 1.042, p = 0.006), moderate to severe dizziness (odds ratio = 2.017, p = 0.034), and moderate to severe anxiety (odds ratio = 2.228, p = 0.017) were independently associated with RD in middle-aged and older adults. Conclusion Older adults exhibited higher incidence of RD after successful treatment for BPPV. Age, moderate to severe dizziness, and moderate to severe anxiety were independent risk factors of RD in middle-aged and older adults.